DRIVING FACTORS OF YOUNG ENTREPRENEURSHIP IN PAPUA - Renouw, Ade Andriani; Meilani, Yohana F. C. Palupi (Faculty of Economics and Business Universitas Pelita Harapan, 2023)
Entrepreneurship is one of the benchmarks for the development of a country and a region. Support is provided by the government for young entrepreneurs, but motivation is needed within themselves to become entrepreneurs. Papua is an area in Indonesia where entrepreneurial growth is quite low. This is the concern of this research. This research focuses on young Papuan entrepreneurs who have become entrepreneurs. The researcher uses a qualitative exploration method to find out what factors support young entrepreneurs to become entrepreneurs. The results of this study indicate that passion is one of the factors that underlie Papuan youth's desire to become entrepreneurs. This research hopes to provide motivation for young people to start a business and for the government to be able to carry out activities that accommodate the results of this research.